First study of the interference between initial and final state radiation at the Z resonance - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1996)
The interference between initial and final state radiation in the process e+e-→μ+μ- at √s≈MZ has been studied by measuring the forward-backward asymmetry as a function of the acoplanarity angle between the final state muons. The interference is expected to be sensitive to the space-time separation of the initial and final state radiation. The measured asymmetry distribution has been compared to theoretical predictions using the koralz generator, with and without Mathematical expression interference. The magnitude of the interference between initial and final state radiation was found to be of the order predicted and to follow the expected distribution. Using the theoretical predictions, a value of Mathematical expression has been extracted. The interpretation of this result is discussed. There is an additional uncertainty in the estimate of ΓZ from as yet uncalculated higher order interference terms. By assuming a value of ΓZ consistent with the world average, the data were used to estimate the size of these uncalculated corrections. © 1996 Springer-Verlag.